Síntese e caracterização de geopolímeros macroporosos com uso de peróxido de hidrogênio - Juliane Valadares e Silva (2019)
The alkaline activated materials with low calcium contents, commonly called geopolymers, are binders obtained through the alkaline activation of materials rich in aluminosilicates, especially metakaolin, a calcined clay with a high content of silica and alumina. The geopolymer properties allow its use in refractories, filters and biotechnology. They can also be used for structural purposes and paving. Geopolymer foam can be aplied in civil construction, and can be used as lightweight building material or insulation. In this work geopolymer foams were produced by the introduction of a foaming agent or bubbles into the geopolymer matrix. The amount and content of surfactant influences the formation, pore volume, porosimetric distribution and morphology. This work aimed to produce and to study a porous geopolymer. The porous geopolymer was produced with metakaolin as the precursor. The mixtures of potassium silicate with potassium hydroxide and also of sodium silicate with sodium hydroxide were evaluated, both using 8 and 10 mol/L hydroxide solution and as foaming agent the hydrogen peroxide was used at different levels. The occurrence of the geopolymerization was evaluated by X-ray diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR). The foam porosity and density characterization was performed by the Archimedes method. Its mechanical properties was evaluated by tests of compression strength. It was observed, through XRD and FTIR that the alkaline activated material went through the geopolymerization reaction with either KOH or NaOH use. The activators molarity variation interfered in porosity, density and mechanical strength of the pastes. The added hydrogen peroxide controls the formation of pores through the release of oxygen and, consequently, the density and mechanical strength of the material.